The association between office design and employee’s productivity at Berjaya Corporation Berhad, Kuala Lumpur / Nurul Atikah Zainuldin - Zainuldin, Nurul Atikah (Faculty of Office Management and Technology, 2016)
The sources of job productivity surrounding are important in which employees spend their working lives. Poor work-life balance or organizational change is the factor that can be as much of a source of pressure as a heavy workload. It has been shown that to have a powerful role in shaping a range of psychological and behavioral outcomes for employees the physical environment that organizations provide for employees to carry out their work activities, most commonly in some form of office space have the effect to the organization. Research by Cooper in 2010 found that 30% troubled that faced by employees physical is because of their working environment. Further, compared to those who were not, employees who were troubled in this way were more likely to have a negative perception of their own levels of positive psychological wellbeing, physical and psychological health, and engagement References to specific workspace features can refer to the large number of work environment studies have shown that workers/users are productive. These lighting, ventilation rates, access to natural light and acoustic environment features preference by users are highly significant to their productivity and workspace satisfaction (Theorell, 1990).